Soccer-Related Concussions Among Swedish Elite Soccer Players: A Descriptive Study of 1,030 Players - Hänni, Sofie; Vedung, Fredrik; Tegner, Yelverton; Marklund, Niklas; Johansson, Jakob (Frontiers in Neurology, 2020)
Objective There are growing concerns about the short- and long-term consequences of sports-related concussion, which account for about 5-9% of all sports injuries. We hypothesized there may be sex differences in concussion history and concussion-related symptoms, evaluated among elite soccer players in Sweden. Design Retrospective survey study. Participants and setting Soccer players (n=1030) from 55 Swedish elite soccer teams. Questionnaires were completed prior to the start of the 2017 season. Assessment of Risk Factors Player history of soccer-related concussion (SoRC), symptoms and management following a SoRC were evaluated. Main Outcome Measures Before the start of the season the players completed a baseline questionnaire assessing previous concussions. The Sports Concussion Assessment Tool 3 was included with regard to symptom evaluation. Results Out of 993 responding players 334 (34.6%) reported a previous SoRC and 103 players (10.4%) reported a SoRC during the past year. After sustaining a SoRC, 114 players (34.2%) reported that they continued their ongoing activity without a period of rest, more commonly female (44.9%) than male players (27.7%; P=0.002). Symptom resolution time was 1 week or less for 61.3% of the players that reported having persisting symptoms. A positive correlation was observed between number of previous concussions and prevalence of three persisting symptoms: fatigue (P<0.001), concentration/memory issues (P=0.002) and headache (P=0.047). Conclusion About 35% of male and female elite soccer players in Sweden have experienced a previous SoRC, and about 10% experienced a SoRC during the last year. Female players continued to play after a SoRC, without a period of rest, more often than males. A higher risk of persisting symptoms was observed in players with a history of multiple concussions.